2007
DOI: 10.1242/jcs.006924
|View full text |Cite
|
Sign up to set email alerts
|

The AAA-ATPase p97-Ufd1-Npl4 is required for ERAD but not for spindle disassembly in Xenopus egg extracts

Abstract: The highly abundant AAA-ATPase p97 is required for diverse cellular processes, of which ER-associated protein degradation (ERAD) is understood best. Previously, a new role of p97 in spindle disassembly at the end of mitosis has been reported. However, we show that neither addition of dominant-negative p97 mutants nor depletion of crucial p97 adaptors impairs transition of meiotic spindles into interphase arrays of microtubules. The dominant-negative approach is validated by inhibition of ERAD, which we reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…S3B to D). Second, we supplemented extract with buffer, wild-type p97 protein, or an ATPase-deficient p97 mutant (p97-DN) shown to act in a dominant-negative manner (45,52,53). Compared to wild-type p97, extract supplemented with p97-DN showed diminished ICL repair and delays in Cdc45 displacement and approach (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3B to D). Second, we supplemented extract with buffer, wild-type p97 protein, or an ATPase-deficient p97 mutant (p97-DN) shown to act in a dominant-negative manner (45,52,53). Compared to wild-type p97, extract supplemented with p97-DN showed diminished ICL repair and delays in Cdc45 displacement and approach (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile another cytosolic protein complex have been found, containing an AAA-ATPase: the mammalian Cdc48p (also termed as p97 or VCP) (Goder et al, 2008;Shcherbik and Haines, 2007;Wilson et al, 2006) may be a key protein in the dislocation process. In complex with two other proteins, Npl4 and Ufd1 (Shcherbik and Haines, 2007;Lass et al, 2008;Cao et al, 2007) that bind ubiquitinated proteins, this complex (Cdc48p-Npl4-Ufd1) (Heubes and Stemmann, 2007;Nowis et al, 2006;Alzayady et al, 2005;Cao and Zheng, 2004) may be responsible for the breakdown of large protein complexes before proteolytic degradation of its elements. Experiments revealed that the process of translocation from ER by Cdc48p-Npl4-Ufd1 is ATP dependent; a comparable function has been attributed to chaperones of the Hsp70 family in importing newly synthesized proteins into the ER and mitochondria (Hood et al, 2003).…”
Section: Proteinsmentioning
confidence: 99%
“…Ufd1-Npl4 has been linked to mitotic spindle disassembly and chromosome segregation [73,74], although this has been disputed recently [75]. These diverse functions raise the question how substrate specificity of the Cdc48/p97…”
Section: Npl4mentioning
confidence: 99%